A Graphene/Poly(3, 4‐ethylenedioxythiophene) Hybrid as an Anode for High‐Performance Microbial Fuel Cells. Issue 8 (21st June 2013) - Wang, Ying; Zhao, Cui‐e; Sun, Dong; Zhang, Jian‐Rong; Zhu, Jun‐Jie
Abstract A microbial fuel cell (MFC) is an innovative power‐output device, which utilizes microorganisms to metabolize fuel and transfers electrons to the electrode surface. In this study, we decorated the surface of graphene (G) with a conducting polymer, poly(3, 4‐ethylenedioxythiophene) (PEDOT), through galvanostatic electropolymerization to fabricate a G/PEDOT hybrid anode for an Escherichia coli MFC. Cyclic voltammetry and electrochemical impedance spectroscopy analyses illustrated that the G/PEDOT hybrid anode possesses a larger active surface area and lower charge‐transfer resistance than three other kinds of anodes, namely, carbon paper (CP), graphene‐modified carbon paper (CP/G), and PEDOT‐modified carbon paper (CP/PEDOT). Scanning electron microscopy was used to investigate the bacteria growth on the four anodes. A compact biofilm was formed on the hybrid anode owing to the electrostatic interaction between the negatively charged bacteria and positively charged PEDOT backbone. The constant‐load (1 KΩ) discharge curves of MFCs with CP, CP/G, CP/PEDOT, and G/PEDOT anodes revealed that the G/PEDOT electrode had good stability and high voltage output. The G/PEDOT anode generated a maximum power density of 873 mW m−2, which is about 15 times higher than that of CP (55 mW m−2) in an H‐shaped dual‐chamber MFC. All the experimental results suggest that the performance of the G/PEDOT hybrid anode is superior to the CP, CP/G, or CP/PEDOT anode.